Kaon Photoproduction: From an Experimental Point of View - Walford, Natalie Kathleen (Makara Journal of Science, 2017)
Today, laboratory experiments conducted worldwide continue to search for undiscovered excited states of the nucleon. The database has been continually updated over the past years to allow for nearly model-independent partial wave analyses (PWA) to be carried out in the search for such undiscovered states. The photoproduction of mesons, such as kaons, has been studied extensively in the past. However, there is still much information that can be gathered and learned from the photoproduction of the kaon. Recent coupled-channel analyses have found strong sensitivity of the K+Λ channel to several higher mass nucleon resonances. Various experiments have provided new and interesting results that are discussed in this short review.